Particles in Contact Micro Mechanics, Micro Process Dynamics and Particle Collective - Antonyuk, Sergiy (Springer International Publishing : Imprint: Springer, 2019)
This book contains the latest scientific findings in the area of granular materials, their physical fundamentals and applications in particle technology focused on the description of interactions of fine adhesive particles. In collaboration between physicists, chemists, mathematicians and mechanics and process engineers from 24 universities, new theories and methods for multiscale modeling and reliable measurement of particles are developed, with a focus on: • Basic physical-chemical processes in the contact zone: particle-particle and particle-wall contacts, • Particle collisions and their dynamics • Constitutive material laws for particle systems on the macro level.